Curriculum innovation implementation for industrialization: A case of education 5.0 pre-service science and mathematics teacher preparation - Matorevhu, Alois (Journal of Research in Instructional, 2023)
Higher and tertiary education graduates in any country should possess job – relevant knowledge and skills to meet needs of industry. Consistent with this, the Ministry of Higher and Tertiary Education, Science, and Technology Development of Zimbabwe, adopted Education 5.0, comprising  five components: teaching, research, community service, innovation, and industrialization.  This case study sought to explore the understanding by science and mathematics teacher educators of Education 5.0 curriculum innovation implementation at 3 teachers’ colleges in Zimbabwe. Science and mathematics teacher educators, purposively sampled participated in focus group discussions. To gain insight on Education 5.0 curriculum innovation implementation, policy documents were analyzed. Emergent themes were interpreted, guided by the interpretivist paradigm, which acknowledges multiple realities. Findings show that science and mathematics teacher educators were positive that Education 5.0 curriculum innovation implementation would cause socio – economic development. However, diverse interpretations of the Education 5.0 curriculum innovation seemed to threaten successful implementation. Therefore, curriculum innovation developers should ensure that implementers understand the envisaged innovation implementation to counter the adverse effects of diverse ontologies. Also, conditions should be conducive to successful curriculum innovation implementation.